Anxiogenic effects of generated ambient cations--a preliminary study - Giannini, A J; Jones, B T; Loiselle, R H; Price, W A (International journal of psychiatry in medicine, 1986)
The existence of the putative "serotonin irritation syndrome" (SIS) was tested in a human population. Volunteers were exposed to a highly cationized environment for two hours. Symptoms of anxiety and excitement significantly increased. During the time of exposure serum serotonin levels also increased significantly. These results support the existence of SIS as a clinical entity.